Determining the Surfactant Consistent with Concrete in order to Achieve the Maximum Possible Dispersion of Multiwalled Carbon Nanotubes in Keeping the Plain Concrete Properties - Mostafa Adresi; Abolfazl Hassani; Soheila Javadian; Jean-Marc Tulliani (Journal of Nanotechnology)
A new surfactant combination compatible with concrete formulation is proposed to avoid unwanted air bubbles created during mixing process in the absence of a defoamer and to achieve the uniform and the maximum possible dispersion of multiwalled carbon nanotubes (MWCNTs) in water and subsequently in concrete. To achieve this goal, three steps have been defined: (1) concrete was made with different types and amount of surfactants containing a constant amount of MWCNTs (0.05 wt%) and the air bubbles were eliminated with a proper defoamer. (2) Finding a compatible surfactant with concrete compositions and eliminating unwanted air bubbles in the absence of a common defoamer are of fundamental importance to significantly increase concrete mechanical properties. In this step, the results showed that the polycarboxylate superplasticizer (SP-C) (as a compatible surfactant) dispersed MWCNTs worse than SDS/DTAB but unwanted air bubbles were removed, so the defoamer can be omitted in the mixing process. (3) To solve the problem, a new compatible surfactant composition was developed and different ratios of surfactants were tested and evaluated by means of performance criteria mentioned above. The results showed that the new surfactant composition (SDS and SP-C) can disperse MWCNTs around 24% more efficiently than the other surfactant compositions.